Gas Chromatographic and Spectroscopic Analyses of Oils of Wild Rubber (Funtumia elastica) Seeds (Biological Sciences - PJSIR, 2007)
. Oi ls from seeds of wi ld rubber ( Funtumia elastica) of different geographical zones i n Ekiti State, Nigeria were an alyzed for fatty acid composi tion u si ng spectroscopic techniq ues v i z: IR, 'H N MR and "C N MR . The oi l conten t of t h e seeds ranged from 43 .3% to 49 .3% with mean of 46.0 ±2.2%. Th e oi ls con si sted of 1 4.33- l 7.77% saturated fatty acids, pal m i t i c and stearic acids and 70.90-88.35% un saturated fatty ac i ds, olei c, l i n ol ci c and l i n ol en i c acids, l i noleic acid bei n g th e m ost abu n dant. Very subtle d i fferences were observed among t h e oi l samples i n the presence of fu n cti ona l grou ps such as tri gl yceride carbon y l , termi nal m ethyl , ol efinic un satu ra ti on and esters. Peaks were obtai ned at 8 2.7 1 -2 .73 and 8 25 .23-27 .60 ppm , show i ng thei r a ll y l i c po i tion s w i th absence of conjugation .